2014
DOI: 10.11607/jop.1204
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Mediates the Relationship Between Pain Interference and Distress in Patients with Persistent Orofacial Pain

Abstract: These results suggest that interventions targeted specifically at fatigue symptoms may be helpful for reducing interference and improving quality of life in patients with persistent orofacial pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…The prevalence of chronic pain steadily increases through age 65, after which it appears to level off (Andersson, 1994; Brattberg, Thorslund, & Wikman, 1989; Verhaak, Kerssens, Dekker, Sorbi, & Bensing, 1998). Chronic pain is a significant health concern and is associated with mortality, reductions in quality of life, and increased feeling of fatigue (Boggero, Kniffin, De Leeuw, & Carlson, 2014; Mobily, Herr, Clark, & Wallace, 1994; Thomas & Roy, 1988; Torrance, Elliott, Lee, & Smith, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic pain steadily increases through age 65, after which it appears to level off (Andersson, 1994; Brattberg, Thorslund, & Wikman, 1989; Verhaak, Kerssens, Dekker, Sorbi, & Bensing, 1998). Chronic pain is a significant health concern and is associated with mortality, reductions in quality of life, and increased feeling of fatigue (Boggero, Kniffin, De Leeuw, & Carlson, 2014; Mobily, Herr, Clark, & Wallace, 1994; Thomas & Roy, 1988; Torrance, Elliott, Lee, & Smith, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the chronic disease severity variable that we used as part of the health composite was based on prescription medications and did not take into account off-label or over-the-counter medication usage. Other measures including sleep, fatigue, and diet have been independently related to pain, cognitive functioning, and disease progression, and their future inclusion will enhance the conceptual framework of how psychological and physiological factors interact to predict health in older adults (Boggero et al, 2013; Koffel et al, 2015; van den Berg-Emons et al, 2007; Watkins et al, 1995; Scarmeas et al, 2009). Future studies should explore whether these variables fully or partially mediate the relationship between task-switching ability and pain on health.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectionally, pain is associated with more physical complaints and poorer health (Demmelmaier, Åsenlöf, Lindberg, & Denison, 2010; Kroenke, Johns, Theobald, Wu, & Tu, 2013; Reyes-Gibby et al, 2002). Pain may impact health through a number of pathways including physical activity, sleep, fatigue, and inflammation, among other mediators (e.g., Boggero, Kniffin, de Leeuw, & Carlson, 2013; Koffel et al, 2015; van den Berg-Emons, Schasfoort, de Vos, Bussmann, & Stam, 2007; Watkins, Maier, & Goehler, 1995). Yet, main effects associating higher pain with poorer health outcomes mask the possibility that older adults may be able to cope with daily pain better at some times than others, with consequences for health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has validated the scale in orofacial pain populations. 7,28 Only the total fatigue score was used in the current study (Cronbach α = .90).…”
Section: Methodsmentioning
confidence: 99%
“…Extant research indicates that orofacial pain disorders are cross-sectionally related to depression, 6 fatigue, 7 and psychological distress, 8 but these relationships are not the same across disorders. Kino and colleagues 9,10 found that myofascial pain patients reported higher depression scores than disc displacement patients.…”
mentioning
confidence: 99%